International journal of reliable and quality e-healthcare - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2012)
The International Journal of Reliable and Quality E-Healthcare (IJRQEH) addresses a variety of issues that relate to the quality and reliability assurance of e-healthcare, patient safety, patient empowerment, and e-medicine. The journal publishes international cutting-edge research and best practices in the field of e-health and quality and reliability assurance. The International Journal of Reliable and Quality E-Healthcare (IJRQEH) encourages international debate on the theoretical and practical aspects of quality, patient safety, and e-health interaction.
"An official publication of the Information Resources Management Association".
Bacon's media directory
Google Scholar
INSPEC
JournalTOCs
MediaFinder
Keywords: Medical care -- Quality control -- Periodicals; Medical informatics -- Periodicals; Telecommunication in medicine -- Periodicals; Quality Assurance, Health Care -- Periodicals; Medical Informatics -- Periodicals; Telemedicine -- Periodicals; Benchmarking and e-health; Clinical Indicators and e-health; Conceptual and historical approach of quality in e-health; E-health knowledge management; Ethics in e-health; Healthcare teams and e-health; Leadership in e-health; Patient safety in e-health; Public e-health informatics; Quality and reliability aspects in evidence based e-medicine; Quality and reliability assurance in mobile health and personalized health systems; Quality and reliability assurance of main telemedicine applications; Quality and reliability for consumer health informatics; Quality and reliability in e-health grids; Quality assurance in e-health; Quality education in e-health; Quality and information technology; Reliability assurance in e-health; Electronic books